Effect of walking and aerobic exercise on physical performance and depression in cases of type 2 diabetes mellitus - Manal K Youssef (SpringerOpen, 2019)
Aim Investigate the effect of walking and aerobic exercise on physical performance and depression symptoms in patient with type 2 diabetes mellitus (T2DM). Patients and methods Forty patients with T2DM were divided into two groups. Group 1 was treated by walking 30 min three times per week. Group 2 was treated by aerobic exercise for 30 min for 3 months. Physical performance and depression were measured pretreatment and posttreatment. Results Walking improved BMI by 4.2%, waist circumference by 1.22%, blood glucose by 6.82%, timed up and go test by 24.34%, static balance by 74.63%, 6 min walk by 14.91%, muscle power by 15.97%, muscle endurance by 71.42%, 2 min stair climbing by 52.63%, squat test by 73.63%, and hospital scale of anxiety and depression by 46.79%. Aerobic exercise improves by BMI 5.47%, waist circumference by 3.95%, blood glucose by 17.21%, time up and go test by 29.2%, static balance by 118.58%, 6 min walk 8.57%, muscle power by 31.93%, muscle endurance by 81.63%, 2 min stair climbing by 49.19%, squat test by 81.3%, and hospital scale of anxiety and depression by 50%. Conclusion Both walking and aerobic exercise improve physical performance and depression scale in T2DM.